PRAGUE - SHIBUYA - BEIJING. NOVELS BY ANNA CIMA AND RADKA DENEMARKOVÁ (NOT ONLY) ABOUT THE FAR EAST - Lollok, Marek (Bohemica Olomucensia, 2020)
The paper Prague - Shibuya - Beijing. Novels by Anna Cima and Radka Denemarková (not only) about the Far East deals with the novels by Radka Denemarková and Anna Cima, which are related by their setting into the Far East countries, namely Japan and China. The analyzes and comparison of both of the novels reveals substantive differences between the plots, characters, aims and strategies of the authors, as well as between the language means applied. In general, despite great ambitions of the Radka Denemarková's extensive novel the Anna Cima's prosaic debute is found as more convincing.
Keywords: contemporary Czech prose; Probudím se na Šibuji; Hodiny z olova; Anna Cima; Radka Denemarková